Why Japan needs English - Morita, Liang (Cogent social sciences, 2017)
This paper argues that Japan needs English, and better English than just knowledge of grammar and vocabulary. English is the main language of globalisation, and there are clear advantages to being proficient in it. For a long time, English has been taught through the grammar-translation method at Japanese schools and universities, which is inadequate to say the least. This has resulted in the inability to work in the English language at the workplace. With a rapidly aging and declining population, the Japanese need to be able to work with foreign co-workers. Being proficient in English would also help the Japanese form alliances and partnerships with foreign establishments in business, research, higher education, and science and technology. This paper also argues that stronger English language skills would help improve attitudes towards foreigners, since recent research has shown that Japanese individuals with stronger English conversation ability have more positive attitudes towards immigration. It would also mitigate discrimination against foreigners if the Japanese could communicate, interact and empathise with them.